Análisis del diseño de instrumentos de evaluación implementados desde dos contextos curriculares - González de Galindo, Susana; Colombo de Cudmani, Leonor (Revista Educación - Journal of Education, 2011)
This research study is part of a more extensive work about the problem of giving new significance to the traditional class of Calculus directed to overcrowded courses of first course in a School of Science. The course is taught using a guide. The idea was to study if there were significant differences in the design of final exams taken by students who had attended the subject in 2001 (when the new methodology was introduced) and the one taken by those who had attended the course in 1999 (traditional teaching). The types of activities were analyzed according to the criteria derived from the theoretical frame and the Standards of Evaluation for the Teaching of Mathematics (NCTM, 1989).The conclusion was that in the 1999 traditional teaching, the activities of the exams aimed to verify if the given acknowledgment had been assimilated. On the contrary, the 2001 activities extensively satisfied the rules established on the Standards of the selected evaluation. This means that there was an important advance in the process of evaluation that had been used.This conclusion confirms the ones obtained from the analysis of other instruments designed to evaluate the new methodological strategy. Teachers are encouraged to introduce this strategy in other contents.